UI/UX Development of Mobile-based Palembang-Indonesia Dictionary application using Design Thinking Method - Indah Sari, Ayu Puspita; Ramdhani, Muhammad Iqbal; Andri, Andri; Oktariansyah, Haris; Mawarni, Mawarni; Novita, Dinda (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
This research aims to develop an optimal User Interface (UI) and User Experience (UX) in a Palembang-Indonesian dictionary mobile application using the Design Thinking method. The background of this study is grounded in the significance of a well-designed UI/UX in enhancing the usability and attractiveness of dictionary applications. Through a literature review, this research analyzes relevant design concepts and principles, and identifies challenges in the development of UI/UX for dictionary applications. The research methodology involves the stages of Design Thinking, encompassing user understanding, problem definition, solution exploration, prototype creation, and testing. The outcomes of this research encompass the development of a more intuitive, efficient, and user-centered UI/UX for the dictionary application. The findings of this research can serve as a guideline for the development of mobile-based dictionary applications, ensuring a favorable user experience. It is expected that this research will make a valuable contribution to the fields of UI/UX and dictionary application development, enhancing accessibility and the quality of dictionary applications for Palembang-Indonesian language users.